The Abca7V1613M variant reduces Aβ generation, plaque load, and neuronal damage - Claire A. Butler; Adrian Mendoza Arvilla; Giedre Milinkeviciute; Celia Da Cunha; Shimako Kawauchi; Narges Rezaie; Heidi Yahan Liang; Dominic I. Javonillo; Annie Thach; Shuling Wang; Sherilyn Collins; Amber Walker; et al. (2024)
Abstract BACKGROUND Variants in ABCA7 , a member of the ABC transporter superfamily, have been associated with increased risk for developing late onset Alzheimer's disease (LOAD). METHODS CRISPR‐Cas9 was used to generate an Abca7 V1613M variant in mice, modeling the homologous human ABCA7 V1599M variant, and extensive characterization was performed. RESULTS Abca7 V1613M microglia show differential gene expression profiles upon lipopolysaccharide challenge and increased phagocytic capacity. Homozygous Abca7 V1613M mice display elevated circulating cholesterol and altered brain lipid composition. When crossed with 5xFAD mice, homozygous Abca7 V1613M mice display fewer Thioflavin S‐positive plaques, decreased amyloid beta (Aβ) peptides, and altered amyloid precursor protein processing and trafficking. They also exhibit reduced Aβ‐associated inflammation, gliosis, and neuronal damage. DISCUSSION Overall, homozygosity for the Abca7 V1613M variant influences phagocytosis, response to inflammation, lipid metabolism, Aβ pathology, and neuronal damage in mice. This variant may confer a gain of function and offer a protective effect against Alzheimer's disease‐related pathology. Highlights ABCA7 recognized as a top 10 risk gene for developing Alzheimer's disease. Loss of function mutations result in increased risk for LOAD. V1613M variant reduces amyloid beta plaque burden in 5xFAD mice. V1613M variant modulates APP processing and trafficking in 5xFAD mice. V1613M variant reduces amyloid beta‐associated damage in 5xFAD mice.